Improved Gas Separation of PEBAX-CSWCNTs Mixed Matrix Membranes - Abbasszadeh Gamali, Pouria; Rahmani, Mohammadreza; Kazemi, Abbass; Pourkhalil, Mahnaz (Journal of Membrane and Separation Technology, 2017)
In the present study, mixed matrix membranes (MMMs) were prepared using PEBAX® 3000 as polymer matrix and single-wall carbon nanotubes (SWCNTs) functionalized with carboxyl groups as nanofillers. The effects of the nanofillers on separation of CO2/N2 and CO2/CH4 were investigated. The pristine PEBAX membrane indicated gas selectivity values of 23 and 13 for CO2/N2 and CO2/CH4, respectively. However selectivity of the modified membrane for gas pairs of CO2/N2 and CO2/CH4 improved to the values of 106.4 and 31.3, respectively. In other words, selectivity of modified membranes compared to those of unmodified ones enhanced greatly. The dramatic increase in gas selectivity of the mixed matrix membranes can be attributed to the polar groups of caboxyl-functionalized single-wall carbon nanotubes (CSWCNTs). While CO2 permeability of MMMs increaesd, permeability of nonpolar gases (N2 and CH4) decreased. FTIR spectra depicted that there were inter/intramolecular forces between ether and amide groups of the polymer chains. For PEBAX membrane filled with 10 wt% CSWCNTs, the peaks of C-O-C، N-H, and H-N-C=O functional groups shifted to lower values due to the formation of hydrogen bonds between polar carboxyl groups of CSWCNTs and amide/ether groups of PEBAX copolymer. Relative crystallinity values of the membranes with various CSWCNTs content were calculated using ΔHf data obtained from DSC measurements. Results demonstared that the rise in content of CSWCNTs brought about the decrement in crystallinity values of polyamide segments. The morphology of the membrane containing 10 wt% CSWCNTs was also investigated emplying AFM images, and a suitable compatability and adhere between PEBAX and CSWCNTs was last confirmed.